Analisis Faktor-Faktor yang Mempengaruhi Kebijakan Dividen pada Perusahaan Publik Sektor Perbankan - Banu Adjie Nugroho; Bambang Purwoko; Edy Supriyadi; Endang Etty Merawati; Derriawan Derriawan; Agus S. Irfani (CV. Rumoh Aceh Publishing, 2026)
This study aims to analyze dividend policy in the banking sector by examining the role of profitability, leverage, and company growth in determining dividend distribution decisions. The research employed a qualitative approach using a case study design to explore the meaning, considerations, and strategic processes underlying dividend policy in Indonesian banking companies. Data were collected through semi-structured interviews, observations, documentation, and triangulation involving banking managers, investors, financial analysts, and academics. The findings reveal that dividend policy is not merely a profit distribution mechanism but also a strategic instrument to maintain investor confidence, corporate reputation, and financial stability. Profitability, represented by Return on Assets (ROA), was perceived as the main indicator of a company’s ability to distribute dividends. Meanwhile, leverage, measured through Debt to Equity Ratio (DER), encouraged firms to adopt more cautious dividend policies to maintain financial resilience. Company growth also influenced dividend decisions, as expanding banks tended to retain earnings to support business development and digital transformation. This study contributes theoretically by providing a qualitative perspective on dividend policy and practically by offering insights for banking management, investors, and policymakers in understanding dividend decision-making dynamics in the banking industry.